PELATIHAN DAN PENERAPAN CHSE DAN K3 BAGI PENGELOLA OBJEK WISATA PEMANDIAN AIR PANAS PADANG GANTING - Fardinal; Ranti Komala Dewi (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Padang Ganting Hot water springs, Tanah Datar regency has experienced a drastic increase in tourist visits in 3 years. Although the problem faced is that visitors often faint due to soaking in hot water and there are even some who are found dead after soaking in hot springs. In addition, visitors' neglect of health protocols in the context of preventing the transmission of Covid-19 while in the bathing area is also a problem that cannot be ruled out. This is exacerbated by the lack of information provided at the bathing location and the incompetence of the management officers in carrying out their respective duties, thereby risking the safety of visitors. Especially now that we are in the Adaptation of New Habits to fight the spread of the Coronavirus, no preventive action has been taken at this tourist attraction which refers to the Covid health protocol. The purpose of this activity is to increase the manager's understanding of K3 and CHSE (cleanliness, health, safety, and environment) at the Padang Ganting Hot Springs tourist attraction. The method of implementing this service activity begins with an initial survey in the field and then continues with Focus Group Discussion activities then training related to the implementation of CHSE (cleanliness, health, safety, environment), installation of occupational safety and health signs and signs calling for the application of CHSE and ends with monitoring and mentoring both directly and online at this tourist attraction. The result of this activity is that managers understand and implement CHSE, the availability of Standard Operating Procedures (SOP) at Padang Ganting hot springs, and the installation of occupational safety and health signs (OSH) and the installation of signboards an appeal for the application of CHSE in Padang Ganting hot springs. So, can avoid the risk of visitors fainting and even dying while soaking in the Padang Ganting Hot Springs.